PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 025 TAMBUSAI KKABUPATEN ROKAN HULU - Yulia, Rosa; Alpusari, Mahmud; ', Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : the results of observation by the author on the study site, it can be seen that the learning outcomes IPA fourth grade students of public school 025 Tambusai yet reached KKM predetermined school is 75, where 32 students only 14 students who reach KKM predetermined with a percentage of 43.750, while 18 people or 56.25% of students still scored below the KKM has been assigned schools, with an average value of 67.66. Instrument research include syllabi, lesson plan, student worksheets. Results of student learning activities and the activities of teachers. Results of the study, showed the presence of peningkatanrata average student learning outcomes, where the base score, an average of only 66.67 student learning outcomes at the end of the first cycle increased to 77.03 an increase of 10.36 points, or 15.54%, and the second cycle into 83.13 with an increase of 16.46 points or 24.69%. Improving student learning outcomes in the classical style, in which the base score is the percentage of student learning outcomes classically produced is 43.75%, in the first cycle increased to 65.63% occurred an increase of 21.98%. Then on the second cycle increased to 93.75% with peningkatar, amounting to 28.12. Increased activity of the teacher in learning, in which the first cycle of the first meeting of the percentage of teacher activity 62.50%, and at the second meeting rose to 70.00, an increase of 7.50%. In the second cycle teachers' meeting three activities increased to 82.50% an increase of 12.50%, and the fourth meeting rose to 97.59, an increase of 15.00%. Increased activity of students, where in the first cycle of the percentage of the first meeting, the student activity only 55.00% and in the second meeting increased to 72.50%. tedadi an increase of 17.50%. Then the second cycle of the third meeting of the percentage of students learning activity increased to 80.00%, an increase of 7.50% compared with the previous meetings, and at the fourth meeting of student learning activities also increased to 95.00% with an increase of 15.00%. the results of the study it can be concluded that the application of cooperative learning model Student Teams Achievement Divisions (STAD) to improve learning outcomes IPA fourth grade students in public primary schools 025 Tambusai Rokan Hulu can improve learning outcomes IPA.Key Words : Cooperative Learning Model Student Teams Achievement Divisions (STAD), IPA Learning Outcomes